2011
DOI: 10.1016/j.exger.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidin lowers brain oxidative stress in adult and middle-aged rats

Abstract: a b s t r a c t a r t i c l e i n f oThere is growing concern over the increasing instances of decline in cognitive abilities with aging in humans. The present study evaluated the benefits of the natural antioxidant, grape seed proanthocyanidin extract (GSPE) in treating the effects of age-related oxidative stress (OS) and accumulation of lipofuscin (LF) on the cognitive ability in rats. Female Wistar rats of 3-and 12-months of age received a daily oral supplement of GSPE until they attained 6-and 15-months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…GSPE has potent antioxidant effects [23][28]. Studies have shown that GSPE have anti-atherosclerotic effects both in animals and human subjects, which has been closely correlated with its antioxidant potency [29].…”
Section: Discussionmentioning
confidence: 99%
“…GSPE has potent antioxidant effects [23][28]. Studies have shown that GSPE have anti-atherosclerotic effects both in animals and human subjects, which has been closely correlated with its antioxidant potency [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that pancreatic beta cells are considered especially susceptible to attacks by oxidative stress because of the very low expression of antioxidant enzymes as compared to other tissues. GSPs were reported to possess a broad spectrum of pharmacological, medicinal and therapeutic properties against oxygen free radicals and oxidative stress [34-36]. So it is still possible that GSPs affect ER stress by preventing oxidative stress on diabetic pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GSPE has demonstrated a wide range of biological effects, including antioxidant (19,20), anti-inflammatory (21,22), anti-mutagenic (23), anti-carcinogenic (24), cardioprotective (25,26) and neuroprotective (27) activities in various experimental models; furthermore, it can effectively reduce ischemia/reperfusion injury (28,29). Moreover, it has been reported to enhance working memory, ameliorate symptoms of Alzheimer’s disease (30), and significantly improve cognitive performance across age groups (31). However, little is known about the potential neuroprotective efficacy of GSPE against pentylenetetrazole (PTZ)-induced seizures.…”
Section: Introductionmentioning
confidence: 99%